Falla cardíaca aguda (2015)
ABSTRACT: We describe the clinical case of a 26 year-old woman who came to Hospital Universitario San Vicente Fundación (Medellín, Colombia) with symptoms and signs of acute heart failure. She had been previously diagnosed with chronic heart failure with reduced ejection fraction without clear origin, pulmonary thromboembolism and ischemic stroke, without optimal neurohormonal modulation. She was admitted with clinical findings of fluid overload and low tissue perfusion, with inotropic support requirement and parenteral diuretics; clinical stability was achieved with the progressive introduction of medical therapy for heart failure. For the study of the latter, heart MRI was done that showed a delayed enhancement area in the left anterior descending artery. Coronary angiography was carried out in which no significant lesions were found in the epicardial arteries. Finally, compensation of the acute heart failure was achieved, and chronic anticoagulation was started for probable thrombophilic disease, due to the recurring arterial and venous thrombotic events.